Poster 144: Minimum 2-year Outcomes after Knotless All-Suture Anchor Bankart Repair. Issue 7 (30th July 2022) - Horan, Marilee; Rakowski, Dylan; Hanson, Jared; Millett, Peter; Pearce, Stephanie
Objectives: Knotless, all suture anchors have significant theoretical and technical advantages such as less bone removal, easier revision, lower profile so less risk for cartilage damage, but clinical results are lacking. The purpose of this study was to report on minimum 2-year outcomes after arthroscopic knotless all-suture Bankart repair in patients with anterior shoulder instability Methods: IRB approval was obtained prior to initiation of this study. Data was collected prospectively and retrospectively reviewed. Patients met inclusion criteria if they were a minimum 2 years out from a Bankart repair using all-suture, knotless anchors (FiberTak anchors) for the repairs by a single surgeon from September 2017 to June 2019. Patients were excluded if they had an anterior labroligamentous periosteal sleeve avulsion, humeral avulsion of the glenohumeral ligament, glenolabral articular disruption lesion, or a rotator cuff repair. Outcome data was collected preoperatively and evaluated at a minimum follow-up of 2 years postoperatively using the American Shoulder and Elbow Surgeons Score (ASES), Single Assessment Numeric Evaluation Score (SANE), Quick Disabilities of the Arm, Shoulder and Hand Score (QuickDASH), the Short Form 12 physical component summary (SF-12 PCS), and patient satisfaction to assess surgical outcomes at final follow-up. Also included are several questions regarding shoulder pain, function and sports participation. Patients with re-dislocations and revision surgery were noted along with any surgical complications. Surgical failure was defined as revision instability surgery, re-dislocation requiring reduction with an ASES score less than 70 or a satisfaction score of 6 or less. Results: A total of 32 patients, 8 females and 24 males, with an average age of 28.5 (SD10.7) years at the time of surgery were included. Postoperative shoulder re-dislocations were reported in 5 cases (15.6%) with 2 patients progressing to a Latarjet (6.0%) at 2 & 3 years post-operatively. There were no postage stamp fractures noted. Moreover, the anchors did not interfere with revision surgery in any way. At final follow-up, mean PRO's significantly improved over preoperative levels. ASES score improved from 58 to 93 (p<0.001), SANE improved from 58-94 (p<0.001), QuickDASH improved from 32.0 to 6.0 (p<0.001) and SF-12 PCS improved from 45.6 to 55.7 (p<0.001). Median postoperative satisfaction was 10/10 (range4-10). Patients reported a significant improvement in shoulder pain during competition (p<.001), and ability to compete in sports (p< .001). There was also significant improvement in painless use of arm for overhead activities (p= .001) and ability to throw a softball 20 yards (p= .001) Conclusions: The arthroscopic treatment of Bankart lesions with knotless all-suture anchors leads to results similar to clinical outcomes to prior studies, with the advantage of ease of revision. Long-term follow-up studies with large patient cohorts will show if the other theoretical advantages of these anchors are born out.